Phase 2 trial of combined cisplatin, etoposide, gemcitabine, and methylprednisolone (PEGS) in peripheral T‐cell non‐Hodgkin lymphoma. Issue 2 (25th July 2012) - Mahadevan, Daruka; Unger, Joseph M.; Spier, Catherine M.; Persky, Daniel O.; Young, Fay; LeBlanc, Michael; Fisher, Richard I.; Miller, Thomas P.
Abstract BACKGROUND: Patients with peripheral T‐cell lymphomas (PTCLs) have inferior progression‐free survival (PFS) and overall survival (OS) compared with patients who have aggressive B‐cell non‐Hodgkin lymphoma. Because PTCLs over express multidrug resistance gene 1/P‐glycoprotein (MDR‐1/P‐gp), we devised platinum, etoposide, gemcitabine, and methylprednisolone (PEGS) with agents that are not substrates of the efflux pump. Gemcitabine was included because of its excellent single‐agent activity in PTCL. METHODS: Patients who had PTCL with stage II bulky disease, stage III or IV disease with extra‐nodal, nodal, and transformed cutaneous presentations were eligible. Patients received intravenous cisplatin 25 mg/m2 on days 1 through 4, etoposide 40 mg/m2 on days 1 through 4, gemcitabine 1000 mg/m2 on day 1, and methylprednisolone 250 mg on days 1 through 4 of a 21‐day cycle for 6 cycles. RESULTS: In total, 34 patients were enrolled, 33 were eligible, and 79% were newly diagnosed. Histologic types were PTCL not otherwise specified (n = 15), anaplastic lymphoma kinase (ALK)‐negative anaplastic large cell lymphoma (n = 4), angioimmunoblastic T‐cell lymphoma (n = 6), or other T‐cell non‐Hodgkin lymphomas (n = 8). Adverse events included 1 grade 5 infection with grade 3 or 4 neutropenia and 9 grade 4 hematologic toxicities. The overall response rate was 39% (47% in PTCL not otherwise specified, 33% in angioimmunoblastic T‐cell lymphoma, 25% in ALK‐negative and 38% in other T‐cell non‐Hodgkin lymphomas). The PFS rate at 2 years was 12% (95% confidence interval, 0.1%‐31%), and the median PFS was 7 months. The OS rate at 2 years was 30% (95% confidence interval, 8%‐54%), and the median OS was 17 months. Immunohistochemical analysis of P‐gp expression revealed strong positivity in a subset of lymphoma cells (n = 6) and tumor endothelium (n = 25). CONCLUSIONS: Overall, PEGS was well tolerated, but OS was not considered promising given the design‐specified targets. These results may serve as a benchmark for future comparisons for non‐CHOP regimens. Cancer 2013. © 2012 American Cancer Society.